Fraud in healthcare facilities: A Narrative Review - Mauren Michaela, Sarah; Nurmalasari, Mieke; Hosizah, Hosizah (Public Health of Indonesia, 2021)
Every country needs to develop Universal Health Coverage (UHC) to promote optimal levels of public health. But in realizing UHC, there must be some problems, one of which is fraud. Based on the Corruption Eradication Commission (KPK) data, potential fraud is detected from 175,774 claims of Advanced Referral Health Facilities (FKRTL) or worth Rp. 440 billion until June 2015. This review article describes the incidence of fraud in health care facilities. Out of a total of 12,736 cases of fraud, readmission occupies the most cases of fraud, which is 4,827 cases or 37.9%.